IMPLEMENTASI PROGRAM KOTA TANPA KUMUH (KOTAKU) DI KABUPATEN SOPPENG - Rusyda, Rusyda; Malik, Ihyani; Syukri, Syukri (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
This study aims to find out how the Implementation of the Cities Without Slums Program in Lilirilau District, Soppeng Regency The type of research used in this research is qualitative research with a descriptive approach. The results of the study show that aspect 1) implementation of program development can be seen from the development of clean/drinking water, environmental road construction, drainage development and waste management which have been benefited by the community. Aspect 2) Implementation Implementation and learning Development program, namely access to clean water, construction of environmental roads, construction of Drainage and Waste Management, Aspect 3) Evaluation of the City Without Slums Program Through the city without slums program, it seeks to establish cooperation between each element to create a city without slums through management waste management and maintaining cleanliness. Supporting factors are in organizational behavior and inhibiting factors. The implementation of the city without slums program still has obstacles, there is still a slum environment that has not been worked on